A history of the latest and Neogene unconformities, offshore Palawan and the southern South China Sea. Issue 8 (1st December 2022) - Luan, Xiwu; Lunt, Peter
Highlights: Major unconformities near Palawan are described and set to a modern time-scale. A history of prior studies and nomenclature is given. The revised tectono-stratigraphy has implications for regional geology. The timing & nature of sedimentary change contradicts tectonic interpretations. Micropalaeontology is an overlooked input to tectonic and basin studies. Abstract: The age and character of the main unconformities offshore Palawan is resolved, and their history reviewed. Some very deep and very shallow unconformities have insufficient well data, but from the Oligocene to Late Miocene times a series of unconformities can be dated, characterised and correlated regionally to help develop a new tectono-stratigraphic framework. This framework does not support the widely cited idea of Early Miocene subduction of a Proto-South China Sea plate followed by collision over a plate suture. The absence or very weak expression of a Base Miocene Unconformity (c. 24 Ma), so strongly expressed across northern Borneo, also suggests a major revision of tectonic models is required. In spite of many cited reports, there is no evidence for an unconformity in the later Early Miocene (c. 17 to 15 Ma), which was a period of gradually increasing compression and uplift. The main mid-Neogene seismic unconformity is the Red Unconformity dated at about 12–13 Ma (equivalent to the DRU of Sabah). This was when the uplift of a foreland over-thrust system paused, and a locally erosional surface was rapidly transgressed. This review describes the neglect of analytical sciences that remain a crucial part of basic geological studies.